COVID-19 and Changes in Reported Social Risk Factors at a Primary Care Practice in the South Bronx - Alexander Azan; Joseph Stephens; Xianhong Xie; Kevin Fiori; Mary Gover (SAGE Publishing, 2023)
Introduction: Historically, Black and Hispanic patient populations in the Bronx Borough of New York City have experienced the highest rates of social risk factors, and associated poor health outcomes, in New York State. During the pandemic, Bronx communities disproportionately experienced high rates of COVID-19 illness and death. To date, little is known regarding the COVID-19 pandemic's impact on social risk factors in urban, at-risk communities. This study aimed to determine how social risk factors changed during the pandemic in a Bronx-based patient population. Methods: Study participants were adult patients seen at a Federally Qualified Health Center in the South Bronx. Using a paired longitudinal study design, 300 participants were randomly selected for telephonic outreach during the pandemic from a sample of 865 participants who had been offered a social risk factor screener in the year prior to the pandemic. The outreach survey used included the social risk factor screener and questions regarding COVID-19 illness burden and prior engagement in social services. The McNemar test was used to analyze trends in reported social risks. Results: Housing quality needs, food insecurity, and legal care needs significantly increased during the pandemic. Participants who reported COVID-19 illness burden were 1.47 times more likely to report a social risk factor ( P  = .02). No significant relationship was found between prior enrollment in clinic-based social services and degree of reported social risk ( P  = .06). Conclusion: Housing quality needs, food insecurity, and legal care needs increased during the COVID-19 pandemic in a predominantly Black and Hispanic identifying urban patient population. Urgently addressing this increase is imperative to achieving health equity in ongoing COVID-19 mitigation efforts.